Blood Flow Disturbance and Morphological Alterations Following the Right Atrial Ligation in the Chick Embryo - Alser, Maha; Salman, Huseyin Enes; Naïja, Azza; Seers, Thomas Daniel; Khan, Talha; Yalcin, Huseyin Cagatay (Frontiers in Physiology, 2022)
Collectively known as congenital heart defects (CHDs), cardiac abnormalities at birth are the most common forms of neonatal defects. Being principally responsible for the heart`s pumping power, ventricles are particularly affected by developmental abnormalities, such as flow disturbances or genomic defects. Hypoplastic Right Heart Syndrome (HRHS) is a rare disease where the right ventricle is underdeveloped. In this study, we introduce a surgical procedure performed on chick embryo, termed right atrial ligation (RAL) for disturbing hemodynamics within the right heart aiming in order to generate an animal model of HRHS. We utilized techniques such as Doppler ultrasound, x-ray micro-CT, histology, and computational fluid dynamics (CFD) analysis, for a comprehensive functional and structural analysis of a developing heart. Our results displayed that RAL does not induce severe flow disturbance and ventricular abnormalities consistent with clinical findings. This study allows us to better understand the hemodynamics-driven CHD development and sensitivities of right ventricles under disturbed flows.